Phytochemical and potential pharmacological properties of Munronia pinnata (Binkohomba): A systematic review - Wijekumar, P.J.; Samaranada, V.A.; Samarakoon, D.N.A.W.; Perera, P.K. (Pharmaceutical Society of Sri Lanka, 2021)
Introduction and objectives: Munronia pinnata is a rare perennial medicinal herb widely used in Sri Lanka, China, and India. It belongs to the family Meliaceae, which has many ecotypes in leaflets such as 3,5,7,9 and 11. M. pinnata is widely used throughout traditional medicine to treat various diseases like fever, general pain, haemorrhoids, dysentery, eczema, cough, asthma, oedema, circulatory diseases, malaria, and vomiting. This systematic review aims to discuss the phytochemical and potential pharmacological properties of the plant. Methods: According to PRISMA guidelines, a comprehensive systematic review was conducted in the following databases; PubMed Central (n=7), Ovid (n=10), Science Direct (n=15), Springer Link (n=11), Cochrane Library (n=1), and Google Scholar (n=170) using “Munronia pinnata” as the keyword. After removing duplicates, the total number of articles was 208. The articles were manually screened for the following inclusion criteria: phytochemical properties and pharmacological properties of M. pinnata. Finally, 21 articles were included for the review. Results: Six of 21 studies reported regarding the phytochemical properties of M. pinnata. The most active phytochemical compounds found in the plant were beta-caryophyllene, caryophyllene oxide, and gandoderiol F. The scientific studies showed following potential pharmacological properties; hypoglycemic (n=7), antioxidant (n=3), anti-inflammatory (n=2), antibacterial (n=2), antifungal (n=1), antimalarial (n=2), hepatoprotective (n=1) and anti-venom (n=3). The toxicological studies showed no toxicity or biochemical and behavioral changes in the experimental models (n=3). Conclusions: The available literature suggests that M. pinnata may have effective pharmacological properties. However, an extensive study is necessary to identify the mechanisms of the properties exhibited by the plant and its wide range of medicinal properties.
Keywords: Pharmacological properties; Munronia pinnata; Systematic review